Des trésors cachés en danger. Études, reconnaissance et valorisation de l’architecture Nachkriegsmoderne (1945-1973) en Autriche - Solène Scherer (In Situ, 2022)
Although many have studied Fin-de-Siècle and Red Vienna (1919-1934) architectures and the authorities have included them in their list of national monuments, Nachkriegsmoderne (post-war modernity) architecture remains to be wholly studied or protected by the Austrian Bundesdenkmalamt (bda). Associations, independent scholars and foundations seem to be taking over from the state/State when it comes to recognising and promoting these poorly appreciated buildings. This article aims to assess the existing measures of protection and regarding this heritage. The comparison of public and private initiatives points to a lack of state validation of those buildings. Thus, private stakeholders’ prevalence in acknowledging this architecture and its importance in Austrian society reveal insufficient public measures towards their preservation.